IT investments and business performance improvement: the mediating role of lean manufacturing implementation - Ghobakhloo, Morteza; Tang, Sai Hong (Taylor & Francis, 2014)
The main purpose of this study is to examine whether the application of current information technology (IT) and different principles of lean manufacturing (LM) are interdependent and complimentary or they are mutually exclusive. This study draws on the so-called IT-enabled organisational capabilities perspective to study the relationships between IT, LM and business performance improvement. Using a questionnaire-based survey, the data come from 231 leading Iranian and Malaysian auto-part manufacturers. The findings suggest that LM and IT are mutually interdependent and value of IT investments can be effectively transformed into business performance improvement for auto-part manufacturers through the higher levels of lean manufacturing system (LMS) implementation. Advanced manufacturing technology (AMT) competency is a valuable intermediate capability which links IT investments into LMS implementation. It was found that IT investment is one of the minimum requirements of LMS implementation for surveyed business, and the value of IT investment is truly transformed to LMS implementation when IT investments offer competent administrative AMTs to effectively manage all production processes. Findings also recommend that managers should avoid isolating the performance metrics only on areas such as net financial measures, while assessing the business value of IT and LM.